Nutritional Deficiencies and Growth Challenges in Underweight Children: A Path to Recovery (International Journal of Food and Nutritional Sciences, 2022)
Underweight in children continues to be a serious public health concern in developing nations, impacting physical and cognitive development as well as general health consequences. One of the main causes of children's stunted growth and development is nutritional inadequacies